Wider rows reduce damage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Planting rice further apart reduces the risk of attacks by the rice gall midge which is a serious pest in Asia and many African countries. The larvae feed on the young rice shoots which then develop the characteristic hollow leaf galls, called...